THE CORRELATION BETWEEN STUDENT’S MOTIVATION AND READING COMPREHENSION IN UNIVERSITAS RIAU KEPULAUAN - Zhamasar, Aisha; Siregar, Alifa Rahmauli; Simanjuntak, Khewin Exando; Dewi, Desi Surlitasari; Amanda, Fid’dia; Reza, Muhammad Khoirul; Az-Zahra, Qanita; Ruslan, Ruslan; Wibowo, Agung Edy; Achmad, Amsakar (JURNAL DIMENSI, 2025)
This study uses a correlational research method, which aims to determine whether there is a significant relationship between motivation and reading comprehension among students at the University of Riau Islands. The participants were 20 students at Universitas Riau Kepulauan, specifically in the English Education Study Program. The study focused on sixth-semester students, as they are expected to have more experience in reading academic texts and are more likely to show clear patterns of motivation and reading comprehension. In this study, two measurement tools were used: a questionnaire and a reading test administered by the teacher to measure students' reading motivation and reading comprehension. In analyzing the data, the questionnaire was scored using a Likert scale. The Shapiro-Wilk test confirmed normal data distribution, and Pearson’s Product-Moment Correlation analysis revealed a negligible negative relationship (r = -0.021, p = 0.930), indicating no significant correlation between motivation and reading comprehension. These results suggest that although motivation is still a crucial aspect of learning, it might not have a direct impact on reading comprehension in this particular situation. In order to obtain deeper insights, future research is encouraged to examine this link using larger samples and a wider range of methodologies.